STUDI KEMAMPUAN TANAH MENYIMPAN AIR TERSEDIA DI SENTRA BAWANG PUTIH KECAMATAN PUJON, KABUPATEN MALANG - Siti Khodijah; S Soemarno (Jurnal Tanah dan Sumberdaya Lahan, 2019)
One of the essential soil resources for garlic cultivation is the soil available water content. The purposes of this study Â were to create pF curves in the garlic areas, to find out the available soil water content, and to find out the impact of pore distribution on available soil water in garlic areas in Pujon, Malang. Parameters observed were soil texture, soil bulk density, soil specific gravity, soil available water content, pF curve, distribution of soil pores and soil porosity. Results of the study showed that there was a specific pF curve at each observation point. Status distribution of soil available water content in garlic areas was high, medium and low. Furthermore, the pore distribution which includes macropores and mesopores was a factor that influenced the soil available water content. The result of this study expected to be able to give beneficial information that can be used as a reference in land management. Also, it is expected that the land management in the garlic areas, Pujon sub-district, Malang will take land mapping unit 2 as the land management to improve the garlic production.